HOLLOW FIBER MEMBRANE MODULE FOR MULTI-COMPONENT GAS SEPARATION: MODELING, SIMULATION AND PROCESS ECONOMICS - SOW MUN, SERENE LOCK (2014)
The widespread expansion of hollow fiber membrane system in industrial gas separation as compared to the traditional techniques is attributed to its environmental advantage as a green technology. The performance of the hollow fiber membrane module has been described by different mathematical models considering that it is an indispensable tool to assist in the design, scale up and optimization of industrial membrane processes. However, there is limited work done in the field of process simulation, whereby mathematical models can be incorporated within commercial process simulators to link the membrane unit with other available unit operations. In addition, the available hollow fiber mathematical models are usually based on ideal binary assumption. Moreover, although commercial hollow fiber membrane modules for gas separation are classified into different flow configurations, most of the mathematical models are confined to merely study of one flow pattern.